2005
DOI: 10.1109/tbme.2005.851507
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrasound Wearable System for the Monitoring and Acceleration of Fracture Healing in Long Bones

Abstract: An ultrasound wearable system for remote monitoring and acceleration of the healing process in fractured long bones is presented. The so-called USBone system consists of a pair of ultrasound transducers, implanted into the fracture region, a wearable device and a centralized unit. The wearable device is responsible to carry out ultrasound measurements using the axial-transmission technique and initiate therapy sessions of low-intensity pulsed ultrasound. The acquired measurements and other data are wirelessly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…It was found that ultrasound propagation velocity increases, while the broadband ultrasound attenuation decreases as the healing process evolves (Floriani et al 1967, Barbieri et al 2011, Protopappas et al 2005. Specifically, in (Protopappas et al 2005) we demonstrated that velocity measurements after 100 days of a sheep osteotomy exceed on average 80% the corresponding intact bone value, while in (Floriani et al 1967) measurements at the 6 th postoperative month on guinea pigs revealed that for completely healed bones the velocity approximated the ratio 94% of the intact bone, respectively. Concerning the early detection of complications, we showed in (Protopappas et al 2005) that the velocity across bones which finally reached bony union was higher than for those with complications even from the 50 th postoperative day.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…It was found that ultrasound propagation velocity increases, while the broadband ultrasound attenuation decreases as the healing process evolves (Floriani et al 1967, Barbieri et al 2011, Protopappas et al 2005. Specifically, in (Protopappas et al 2005) we demonstrated that velocity measurements after 100 days of a sheep osteotomy exceed on average 80% the corresponding intact bone value, while in (Floriani et al 1967) measurements at the 6 th postoperative month on guinea pigs revealed that for completely healed bones the velocity approximated the ratio 94% of the intact bone, respectively. Concerning the early detection of complications, we showed in (Protopappas et al 2005) that the velocity across bones which finally reached bony union was higher than for those with complications even from the 50 th postoperative day.…”
Section: Discussionmentioning
confidence: 53%
“…Specifically, in (Protopappas et al 2005) we demonstrated that velocity measurements after 100 days of a sheep osteotomy exceed on average 80% the corresponding intact bone value, while in (Floriani et al 1967) measurements at the 6 th postoperative month on guinea pigs revealed that for completely healed bones the velocity approximated the ratio 94% of the intact bone, respectively. Concerning the early detection of complications, we showed in (Protopappas et al 2005) that the velocity across bones which finally reached bony union was higher than for those with complications even from the 50 th postoperative day. Additionally, the study of (Ferreira et al 2010) on pseudarthrosis in rats showed that AIB values for pseudarthrosis were higher comparing to intact bone.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations